Inflammation context in Alzheimer's disease, a relationship intricate to define - Novoa, Catalina; Salazar, Paulina; Cisternas, Pedro; Gherardelli, Camila; Vera-Salazar, Roberto; Zolezzi Moraga, Juan Manuel; Inestrosa, Nibaldo C. (My University, 2022)
Alzheimer's disease (AD), the most common form of dementia, is characterized by the accumulation of amyloid beta (A beta) and hyperphosphorylated tau protein aggregates. Importantly, A beta and tau species are able to activate astrocytes and microglia, which release several proinflammatory cytokines, such as tumor necrosis factor alpha (TNF-alpha) and interleukin 1 beta (IL-1 beta), together with reactive oxygen (ROS) and nitrogen species (RNS), triggering neuroinflammation. However, this inflammatory response has a dual function: it can play a protective role by increasing A beta degradation and clearance, but it can also contribute to A beta and tau overproduction and induce neurodegeneration and synaptic loss. Due to the significant role of inflammation in the pathogenesis of AD, several inflammatory mediators have been proposed as AD markers, such as TNF-alpha, IL-1 beta, Iba-1, GFAP, NF-kappa B, TLR2, and MHCII. Importantly, the use of anti-inflammatory drugs such as NSAIDs has emerged as a potential treatment against AD. Moreover, diseases related to systemic or local inflammation, including infections, cerebrovascular accidents, and obesity, have been proposed as risk factors for the development of AD. In the following review, we focus on key inflammatory processes associated with AD pathogenesis.
Keywords: Proinflammatory cytokine; Pathogenesis